High adhesive epoxy glue and preparation method thereof
Patent Information
- Application Number
- CN202611428085.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-30
AI Technical Summary
部分快固化体系反应活性过高,胶水混合之后可操作时间极短,还未充分流平浸润基材表面就发生凝胶固化,有效粘接面积得不到保障,最终实际剪切强度大幅降低
(一)本发明采用MABS与环氧树脂高温熔融分散制备得到预聚树脂,MABS内部丁二烯橡胶相以微相形式分散于环氧基体中,可有效吸收应力、钝化裂纹,解决传统环氧胶固化后脆性大的缺陷,胶层断裂伸长率可达10%以上。同时MABS分子自带极性基团,有效提升对PC、PET塑料基材的界面附着力,搭配硅烷偶联剂进一步强化金属、PCB基材界面结合,实现PC/PC、PET/PET剪切强度5MPa,铝铝剪切强度大于10MPa,能够满足PCB板、FPC连接器补强粘接对力学性能的要求。
Smart Images

Figure SMS_28 
Figure SMS_29 
Figure SMS_30
Abstract
Description
Technical Field
[0001] This invention belongs to the field of adhesive technology, specifically relating to a high-adhesion epoxy adhesive and its preparation method. Background Technology
[0002] As electronic components become increasingly miniaturized and high-density, the bonding and reinforcement of rigid printed circuit boards (PCBs) and flexible printed circuit boards (FPCs) has become a critical process in electronic assembly. The adhesives used in this process not only need high bonding strength but also good flexibility, while maintaining a reasonable curing speed and weather resistance to withstand the complex conditions of component deformation and temperature fluctuations during operation. While general-purpose epoxy adhesives on the market currently meet basic bonding requirements, the cured adhesive layer is rigid, has low elongation at break, and is generally brittle. When the substrate undergoes slight deformation or is subjected to external stress, the adhesive layer is prone to cracking or debonding at the bonding interface, making it difficult to meet the reinforcement bonding requirements of easily deformable substrates such as PCBs and FPCs.
[0003] Existing fast-curing epoxy adhesives still have several shortcomings. Some fast-curing systems are too reactive, resulting in an extremely short workable time after mixing. They gel and cure before fully leveling and wetting the substrate surface, failing to guarantee an effective bonding area and ultimately significantly reducing the actual shear strength. Other systems exhibit violent exothermic curing reactions, which, under conditions of large adhesive layer thickness, easily generate air bubbles within the adhesive layer, causing internal defects and severely compromising the mechanical properties of the bonded joint, directly affecting the stability of electronic products.
[0004] Current toughening and modification methods for epoxy adhesives also have significant limitations. Many toughening components have poor compatibility with epoxy resin matrices, easily leading to turbidity after mixing. This not only damages the translucency of the adhesive layer but also weakens its adhesion to plastic substrates such as PC and PET. After high-temperature, low-temperature, humid-heat, and high-low-temperature cycling aging, the bond strength decreases significantly, making it difficult to pass the stringent reliability tests of the electronics industry. For the actual bonding and reinforcement of PCB boards and FPC connectors, existing products struggle to simultaneously achieve high bond strength, excellent flexibility, a controllable curing window, and long-term aging resistance. Therefore, developing a high-adhesion epoxy adhesive with superior overall performance is of significant practical importance in addressing the practical pain points of bonding and reinforcement in electronic components. Summary of the Invention
[0005] To solve the above-mentioned technical problems, the first aspect of the present invention provides a high-adhesion epoxy adhesive, the raw materials of which include component A and component B. Component A has a viscosity of 30,000-35,000 cps at 22°C, and component B has a viscosity of 10,000-15,000 cps at 22°C.
[0006] As an feasible example, the raw materials for preparing component A, by mass percentage, include 20-30% prepolymer resin, 60-70% epoxy resin, 8-10% reactive diluent, and 1-2% silane coupling agent, with the sum of the mass percentages of the raw materials for preparing component A being 100%; the raw materials for preparing component B, by mass percentage, include 80-95% rapid curing agent, 5-12% slow curing agent, and 1-5% catalyst, with the sum of the mass percentages of the raw materials for preparing component B being 100%.
[0007] As an feasible example, the prepolymer resin has a viscosity of 100,000-120,000 cps at 25°C, and the raw materials for preparation include epoxy resin and MABS plastic particles (methyl methacrylate). Acrylonitrile butadiene (Styrene copolymer). Further, in the raw materials for preparing the prepolymer resin, the mass ratio of epoxy resin to MABS plastic particles is (88-90):(10-12). Even further, the preparation method of the prepolymer resin is as follows: heat the epoxy resin to 180℃, then slowly add MABS plastic particles in multiple batches (the particles can be crushed using a material grinder before addition, which helps accelerate melting and dispersion). The amount added should not exceed 12% of the epoxy resin addition; exceeding this ratio will exceed the saturation absorption capacity of the resin system, resulting in uneven particle dispersion. Continue stirring for about 2 hours; the time should not be too long, otherwise it will aggravate the yellowing phenomenon. Vacuum stir for 3 minutes to remove air bubbles, filter, and the prepolymer resin is obtained.
[0008] In the raw material system, prepolymer resin mainly plays a role in toughening, improving substrate adhesion, and adapting to processing technology. On the one hand, the butadiene rubber phase contained in MABS can form a stress-absorbing microphase structure in the epoxy matrix, effectively improving the problem of high brittleness of the adhesive layer after pure epoxy curing, increasing the elongation at break of the adhesive layer, resisting deformation stress caused by vibration and high and low temperature cycling, and preventing cracking of the adhesive layer. On the other hand, the polar groups in MABS molecules can enhance the interfacial bonding force of the adhesive to plastic substrates such as PC and PET, avoid interfacial damage, and improve shear bond strength. At the same time, the viscosity of the prepolymer resin is controlled at 100,000 at 25℃. With 120,000 cps and an MABS addition amount not exceeding 12% of the epoxy resin mass, this method ensures sufficient melting and dispersion of MABS to achieve its toughening and adhesion-enhancing effects, while avoiding excessive viscosity that could affect application. It also prevents uneven dispersion caused by exceeding the resin system's saturation absorption capacity. The high-temperature melt prepolymerization method also avoids the drawbacks of direct physical blending of MABS, such as phase separation and particle precipitation, resulting in a homogeneous and stable adhesive system. Furthermore, compared to small-molecule liquid toughening agents, the prepolymerized resin provided by this invention is less prone to migration and precipitation, which helps ensure the long-term reliability of the adhesive layer under aging conditions such as high temperature, low temperature, and humid heat. Meanwhile, the matrix bonding strength and cross-linking basis are still provided by the epoxy resin in the system.
[0009] As an implementable example, the reactive diluent is an aliphatic diglycidyl ether, selectable from 1,4-butanediol diglycidyl ether, 1,6-butanediol diglycidyl ether, etc. At least one of hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, diethylene glycol diglycidyl ether, and cyclohexanediethanol diglycidyl ether; preferably the bifunctional reactive diluent 1,4-butanediol diglycidyl ether, which can avoid the problems of decreased crosslinking density, deterioration of bonding strength and aging resistance caused by the use of a large amount of monofunctional reactive diluent.
[0010] As an implementable example, the silane coupling agent includes an epoxy-based silane coupling agent, preferably 3... (2,3 Epoxypropyltrimethoxysilane (KH) 560), 3 (2,3 Epoxypropyltriethoxysilane, mercaptosilane coupling agent KH 590. Diaminosilane coupling agent KH At least one of 792, more preferably KH 560. KH 560 is an epoxy-based silane coupling agent; the epoxy groups on its molecular chain can participate in epoxy resin coupling. The cross-linking reaction of the curing agent system bonds into the cured adhesive layer network. After hydrolysis, the siloxane groups in the molecule can form chemical bonds with the hydroxyl groups on the surface of aluminum and PCB substrates, which enhances the interfacial bonding force between the adhesive layer and the substrate, inhibits the intrusion of moisture into the bonding interface, and improves the adhesion strength retention rate under humid heat and high and low temperature cycling aging conditions.
[0011] As an feasible example, the rapid curing agent is a polythiol-based curing agent, preferably GL1800 curing agent from Guangzhou Geling New Material Co., Ltd. This polythiol curing agent can rapidly react with epoxy resin to form mercapto groups under the action of a catalyst. The epoxy addition reaction imparts rapid curing capability to the epoxy adhesive system. The slow-curing agent is a primary amine-terminated polyoxypropylene compound, preferably ZD-123 curing agent. This primary amine-terminated polyoxypropylene compound combines flexible polyether segments with reactive amino groups. When used in combination with polythiol curing agents, it can moderately slow down the gelation rate of the system, broaden the workable application window of the adhesive, and avoid the defects of excessively short working time, intense exothermic curing, and blistering of thick adhesive layers caused by using a single polythiol curing agent. Furthermore, this curing agent reacts well with epoxy... The polythiol system has good compatibility and helps to improve the adhesion performance of the adhesive layer to the plastic substrate.
[0012] As an implementable example, the catalyst comprises N,N-dimethyldipropyltriamine, which is a tertiary amine catalyst capable of catalyzing the mercapto group between polythiol and epoxy resin. The epoxy addition reaction regulates the curing rate of the system, enabling components A and B to achieve functional curing in a short time after mixing. Its synergistic effect when combined with a polythiol fast-curing agent and a primary amino alcohol-terminated polyoxypropylene slow-curing agent can maintain the adhesive's working time at 5 minutes and control the functional curing time at 10 minutes. The 15-minute curing time satisfies the rapid curing requirements for bonding and reinforcing PCB boards and FPC connectors while maintaining a reasonable curing window. Furthermore, based on the total mass of component B, N, N The mass percentage of dimethyldipropyltriamine is 2%. The catalyst dosage is 4%, preferably 3%. If the catalyst dosage is too low, the catalytic activity will be insufficient, which will slow down the curing reaction and prolong the curing cycle; if the catalyst dosage is too high, the reaction rate will be too fast, the operating window will be shortened, the curing exothermic effect will be aggravated, and problems such as bubbles and decreased bonding strength will easily occur.
[0013] The first aspect of this invention provides a method for preparing a high-adhesion epoxy adhesive, comprising the following steps: S1. Set the reactor heating temperature to 60℃, add the prepolymer resin, epoxy resin, reactive diluent and silane coupling agent into the reactor in sequence and stir for 2 hours, then filter to obtain component A. The fast curing agent, slow curing agent, and catalyst were added sequentially to another reactor and stirred for 2 hours. The mixture was then filtered to obtain component B. S2. Mix component A and component B, preferably in a mass ratio of 100:100, to obtain a high-adhesion epoxy adhesive.
[0014] Beneficial effects (I) This invention uses high-temperature melt dispersion of MABS and epoxy resin to prepare a prepolymer resin. The butadiene rubber phase within the MABS is dispersed in the epoxy matrix as a microphase, effectively absorbing stress and passivating cracks, thus solving the problem of high brittleness after curing traditional epoxy adhesives. The elongation at break of the adhesive layer can reach over 10%. Simultaneously, the MABS molecules possess polar groups, effectively improving interfacial adhesion to PC and PET plastic substrates. Combined with a silane coupling agent, this further strengthens the interfacial bonding between metal and PCB substrates, achieving a shear strength of 5 MPa for PC / PC and PET / PET, and for aluminum... Aluminum has a shear strength greater than 10MPa, which can meet the mechanical performance requirements for reinforcing and bonding PCB boards and FPC connectors.
[0015] (II) This invention employs a combination of a rapid-curing polythiol agent and a slow-curing primary amine-terminated polypropylene oxide agent, along with a tertiary amine catalyst to synergistically regulate the reaction rate. This overcomes the drawback of the short working time of a single polythiol curing agent, achieving a 5-minute workable time and a 10 15-minute functional curing. The adhesive has sufficient time to flow and wet the substrate after mixing, ensuring an effective bonding area. This meets the rapid operation requirements of electronic production lines while avoiding problems such as bonding failure and air bubbles in thick adhesive layers caused by excessively rapid gelation.
[0016] (III) This invention disperses MABS in an epoxy resin matrix using a 180℃ high-temperature melt prepolymerization process, avoiding the problems of phase separation and particle precipitation caused by direct physical blending; ZD 123 Primary amino alcohol-terminated polyoxypropylene curing agent and epoxy The polythiol system has excellent compatibility. After mixing components A and B, the adhesive solution is uniform and clear, without any turbidity or stratification, ensuring the appearance quality of the adhesive layer and meeting the appearance requirements of electronic products.
[0017] (iv) In the prepolymer resin, MABS is anchored to the epoxy network in a microphase structure and will not migrate and precipitate like small molecule toughening agents; in KH The synergistic effect of 560 coupling agent inhibits the penetration of water vapor into the bonding interface. After being subjected to high temperature of 85℃... After testing at 40℃ low temperature, 85℃ / 85%RH humid heat, high and low temperature cycling, and xenon lamp aging, the adhesive strength retention rate is high, and the adhesive layer shows no cracking, blistering, yellowing, or powdering, and can withstand long-term alternating operating conditions of electronic devices.
[0018] (v) The preparation conditions of components A and B are mild, requiring only stirring and filtration at 60°C. The prepolymer resin preparation process is controllable, and the viscosity index is easy to control. The mass ratio of components A and B is 100:100, which is simple and convenient for gluing operations. It is suitable for electronic assembly processes such as dispensing and can be directly used for bonding and reinforcing PCB boards and FPC connectors. Detailed Implementation
[0019] Example 1 The first aspect of this example provides a high-adhesion epoxy adhesive, the raw materials of which include component A and component B. The raw materials of component A, by mass percentage, include 25% prepolymer resin, 65% 128 epoxy resin (Nanya 128 epoxy resin), 9% reactive diluent 1,4-butanediol diglycidyl ether, and 1% silane coupling agent KH560. The raw materials of component B, by mass percentage, include 90% rapid curing agent GL1800 (purchased from Guangzhou Geling New Material Co., Ltd.), 7% slow curing agent ZD-123 (supplied by Huntsman Corporation), and 3% catalyst N,N-dimethyldipropyltriamine.
[0020] The prepolymer resin has a viscosity of 100,000-120,000 cps at 25°C. The raw materials include 128 epoxy resin and MABS plastic particles (Chimei Chemical PA-758), with a mass ratio of 90:10 between the 128 epoxy resin and the MABS plastic particles. The prepolymer resin is prepared by heating the epoxy resin to 180°C, then slowly adding the MABS plastic particles in multiple portions, stirring continuously for about 2 hours, followed by vacuum stirring for 3 minutes to remove air bubbles, and filtering to obtain the prepolymer resin.
[0021] The second aspect of this example provides a method for preparing a high-adhesion epoxy adhesive, including the following steps: S1. Set the reactor heating temperature to 60℃, add the prepolymer resin, 128 epoxy resin, reactive diluent and silane coupling agent into the reactor in sequence and stir for 2 hours, then filter to obtain component A. The fast curing agent, slow curing agent, and catalyst were added sequentially to another reactor and stirred for 2 hours. The mixture was then filtered to obtain component B. S2. Mix component A and component B at a mass ratio of 100:100 to obtain a high-adhesion epoxy adhesive.
[0022] This invention also provides a method for using a high-adhesion epoxy adhesive. When the epoxy adhesive obtained in Example 1 is applied to PCB boards and FPC connector bonding and reinforcement applications, the following process is recommended: 1. Pretreatment of bonding surfaces: Wipe the bonding surfaces with isopropanol or acetone to remove oil, then wipe them dry with a clean, lint-free cloth. If necessary, dry with hot air at 40-60℃ for 10-15 minutes to ensure that there is no oil, dust and moisture residue on the substrate surface. 2. Mixing: Take out component A and component B at a mass ratio of 100:100 and add them to a clean mixing container. It is recommended to mechanically stir at 300-500r / min for 2-3 minutes until the color of the adhesive is uniform. 3. Coating conditions: Apply adhesive using an automatic dispensing machine or a scraper. Recommended adhesive application rate is 50-200 g / m² on one side. 2The adhesive layer thickness should be controlled between 0.05-0.30mm; the dispensing pressure should be 0.2-0.4MPa, and the needle diameter should be 0.3-0.8mm to avoid defects such as insufficient adhesive, broken adhesive, or excessively thick adhesive layer. 4. Curing conditions: Functional curing time is 10-15 minutes at room temperature (25℃±5℃), and complete curing time is 24 hours; if accelerated curing is required, it can be baked at 40-60℃ for 30-60 minutes before the next process. 5. Operating temperature range: After curing, the adhesive layer has been tested and can be used for a long time in the temperature range of -40℃ to 85℃, and can withstand 200 cycles of high and low temperature at -40℃ / 85℃ without cracking; 6. Storage and disposal of leftover adhesive: Components A and B should be sealed and stored in a dry environment at 8-28℃ in an unopened state, away from light, with a shelf life of 6 months; any unused adhesive after mixing should not be returned to the bottle for further use as it has already undergone a curing reaction.
[0023] The physicochemical properties of components A and B before curing in this example are tested and detailed in Table 1.
[0024] Table 1
[0025] In this example, the working time for the high-adhesion epoxy adhesive is 5 minutes, the functional curing time is 10-15 minutes, and the complete curing time is 24 hours. The mechanical properties of the high-adhesion epoxy adhesive are detailed in Table 2, and the weather resistance properties are detailed in Table 3.
[0026] Table 2
[0027] Table 3
[0028] Test method descriptions: Shear strength test refers to GB / T 7124; tensile property test refers to GB / T 1040.2; xenon lamp aging test refers to GB / T 16422.2; damp heat aging test refers to GB / T 2423.3.
[0029] Comparative Example 1 (No prepolymer resin system) The specific implementation method in this example is the same as in Example 1, except that an equal amount of 128 epoxy resin is used to replace the prepolymer resin.
[0030] Results: The elongation at break decreased from >10% to <5%, the epoxy resin became brittle, and the shear strength of PC / PC decreased from 5MPa to about 3MPa (interfacial failure).
[0031] Comparative Example 2 (using only a single polythiol-based rapid curing agent) The specific implementation method of this example is the same as that of Example 1, except that curing agent 2 (ZD-123) in component B is completely replaced with curing agent 1 (Guangzhou Geling GL1800). That is, the raw materials for the preparation of component B are: GL1800 curing agent 97% + catalyst N,N-dimethyldipropyltriamine 3% by mass percentage.
[0032] Results: The operation time was reduced from 5 minutes to less than 2 minutes. The construction window was too narrow, and the glue began to gel before it could flow and level, resulting in insufficient bonding area and a decrease in shear strength of about 30%. At the same time, the curing exothermic effect was intense, and air bubble defects appeared in the thick glue layer.
[0033] Comparative Example 3 (imbalance between fast-curing agent and slow-curing agent ratio) The specific implementation method in this example is the same as in Example 1, except that the mass percentage of the fast curing agent (GL1800) in component B is reduced from 90% to 60%, and the mass percentage of the slow curing agent (ZD-123) is increased from 7% to 37%.
[0034] Results: The functional curing time increased from 10-15 min to over 60 min, failing to meet the requirements for rapid curing; furthermore, the crosslinking density after curing was insufficient, and the aluminum / aluminum shear strength decreased from >10 MPa to approximately 6 MPa. This indicates that the mass ratio of rapid curing agent to slow curing agent (approximately 13:1) has a significant impact on rapid curing performance and bond strength.
[0035] Comparative Example 4 (using other types of curing agents) The specific implementation method in this example is the same as in Example 1, except that an equal amount of polyamide curing agent is used to replace the ZD-123 curing agent in component B.
[0036] Results: The system compatibility deteriorated, the mixture of components A and B became cloudy, and the light transmittance of the cured adhesive layer decreased; the PET / PET shear strength decreased from 5 MPa to about 4 MPa, indicating that the primary amino alcohol-terminated polypropylene oxide structure of ZD-123 curing agent contributes to the compatibility with the epoxy-polythiol system and the adhesion to the plastic substrate.
[0037] Comparative Example 5 (prepolymer resin viscosity deviates from the scope of the invention) The specific implementation method in this example is the same as in Example 1, except that the mass percentage of MABS plastic particles added to the prepolymer resin is reduced from 10% to 4% (the mass ratio of 128 epoxy resin to MABS in the prepolymer resin is changed from 90:10 to 96:4), so that the viscosity of the obtained prepolymer resin at 25°C is reduced from the specified range of 100,000-120,000 cps to about 50,000 cps.
[0038] Results: The MABS toughening rubber phase content in the prepolymer resin was insufficient to form a complete stress relaxation network, resulting in decreased interfacial affinity with PC and PET plastic substrates. After curing, the elongation at break of the adhesive layer decreased from >10% to approximately 6%, the PC / PC shear strength decreased from 5 MPa to approximately 4 MPa, and the PET / PET shear strength decreased from 5 MPa to approximately 4.2 MPa. Furthermore, the shear strength retention rate after 80℃×500h heat aging decreased to approximately 80%. This indicates that the viscosity of the prepolymer resin at 25℃ (essentially reflecting the amount of MABS added) has a significant impact on both the flexibility and adhesive strength of the epoxy adhesive. Therefore, by limiting the viscosity of the prepolymer resin to 100,000-120,000 cps and matching the MABS addition amount in the prepolymer resin to 10-12% of the mass of 128 epoxy resin, this invention can simultaneously achieve both toughening and adhesive effects.
[0039] Comparative Example 6 (MABS plastic particle physical properties deviate from the scope of the invention) The specific implementation method of this example is the same as that of Example 1, except that: commercially available general-purpose ABS plastic particles (Chimei Chemical PA-757, acrylonitrile content of about 24%, melt flow rate of about 1.8 g / 10 min, butadiene rubber phase content of about 12%, without MMA unit) are used to replace MABS plastic particles (Chimei Chemical PA-758) to prepare prepolymer resin, while the rest of the process remains the same.
[0040] Results: General-purpose ABS lacks MMA and AN polar units, resulting in weak interphase bonding between the two phases after melt dispersion with the 128 epoxy resin matrix. Component A showed slight turbidity after 72 hours at 25°C. Simultaneously, the butadiene rubber phase content was relatively low, leading to insufficient toughening effect. The shear strength of PC / PC decreased from 5 MPa to approximately 4.2 MPa, and the shear strength of PET / PET decreased from 5 MPa to approximately 4 MPa. After 168 hours of humid heat aging at 85°C / 85%RH, the proportion of interfacial damage to the PET substrate increased from approximately 10% to approximately 30%. This indicates that the MMA / AN polar units contained in MABS have a significant impact on the compatibility of the adhesive and its interfacial adhesion to the plastic substrate. Therefore, this invention, by explicitly limiting the use of MABS and selecting appropriate grades of MABS plastic particles, can ensure the uniform compatibility of component A and long-term bonding reliability.
Claims
1. A high-adhesion epoxy adhesive, characterized in that, The raw materials for preparation include component A and component B; The viscosity of component A at 22°C is 30,000-35,000 cps, and the viscosity of component B at 22°C is 10,000-15,000 cps. The raw materials for preparing component A, by mass percentage, include 20-30% prepolymer resin, 60-70% epoxy resin, 8-10% reactive diluent, and 1-2% silane coupling agent, and the sum of the mass percentages of the raw materials for preparing component A is 100%. The raw materials for preparing component B, by mass percentage, include 80-95% fast curing agent, 5-12% slow curing agent, and 1-5% catalyst, and the sum of the mass percentages of the raw materials for preparing component B is 100%.
2. The high-adhesion epoxy adhesive according to claim 1, characterized in that, The prepolymer resin has a viscosity of 100,000-120,000 cps at 25°C, and the raw materials for its preparation include epoxy resin and MABS plastic particles.
3. The high-adhesion epoxy adhesive according to claim 2, characterized in that, In the raw materials for preparing the prepolymer resin, the mass ratio of epoxy resin to MABS plastic particles is (88-90):(10-12).
4. The high-adhesion epoxy adhesive according to claim 2, characterized in that, The preparation method of the prepolymer resin is as follows: heat the epoxy resin to 180°C, add MABS plastic particles, stir continuously for 2 hours, vacuum stir for 3 minutes, remove bubbles, filter, and the prepolymer resin is obtained.
5. The high-adhesion epoxy adhesive according to claim 1, characterized in that, The active diluent is an aliphatic diglycidyl ether, selected from 1,4-butanediol diglycidyl ether, 1,6-butanediol diglycidyl ether, etc. At least one of hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, diethylene glycol diglycidyl ether, and cyclohexanediethanol diglycidyl ether.
6. The high-adhesion epoxy adhesive according to claim 1, characterized in that, The silane coupling agent comprises 3 (2,3 3-(2 ... (2,3 Epoxypropoxypropyltriethoxysilane, KH 590 silane coupling agent, KH At least one of 792 silane coupling agents.
7. The high-adhesion epoxy adhesive according to claim 1, characterized in that, The rapid curing agent is a polythiol-based curing agent.
8. The high-adhesion epoxy adhesive according to claim 1, characterized in that, The slow-curing agent is a primary amine alcohol-terminated polyoxypropylene compound.
9. The high-adhesion epoxy adhesive according to claim 1, characterized in that, The catalyst includes N,N-dimethyldipropyltriamine.
10. A method for preparing a high-adhesion epoxy adhesive according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Set the reactor heating temperature to 60℃, add the prepolymer resin, epoxy resin, reactive diluent and silane coupling agent into the reactor in sequence and stir for 2 hours, then filter to obtain component A. The fast curing agent, slow curing agent, and catalyst were added sequentially to another reactor and stirred for 2 hours. The mixture was then filtered to obtain component B. S2. Mix component A and component B to obtain a high-adhesion epoxy adhesive.
